Highly Biocompatible Carbon Nanodots for Simultaneous Bioimaging and Targeted Photodynamic Therapy In Vitro and In Vivo. (17th July 2014) - Choi, Yuri; Kim, Seongchan; Choi, Myung‐Ho; Ryoo, Soo‐Ryoon; Park, Jongnam; Min, Dal‐Hee; Kim, Byeong‐Su
<x xml:space="preserve">Abstract</x> Photosensitizers (PSs) are light‐sensitive molecules that are highly hydrophobic, which poses a challenge to their use for targeted photodynamic therapy. Hence, considerable efforts have been made to develop carriers for the delivery of PSs. Herein, a novel design is described of highly biocompatible, fluorescent, folic acid (FA)‐functionalized carbon nanodots (CDs) as carriers for the PS zinc phthalocyanine (ZnPc) to achieve simultaneous biological imaging and targeted photodynamic therapy. FA is modified on PEG‐passivated CDs (CD‐PEG) for targeted delivery to FA‐positive cancer cells, and ZnPc is loaded onto CD‐PEG‐FA via π–π stacking interactions. CD‐PEG‐FA/ZnPc exhibits excellent targeted delivery of the PS, leading to simultaneous imaging and significant targeted photodynamic therapy after irradiation in vitro and in vivo. The present CD‐based targeted delivery of PSs is anticipated to offer a convenient and effective platform for enhanced photodynamic therapy to treat cancers in the near future.